Organic residue controls Meloidogyne javanica and improves gas exchange and development in the gilo - Santos, Luam; Silva, Rodrigo Vieira; Pedro Elias Gondim, João; Eduardo Rodrigues, Rhayf; Leonardo Ferreira, Luis (Revista Ciência Agronômica, 2023)
Root-knot nematodes cause a significant reduction in the productivity of the gilo due to physiological stress. Incorporating organic residue into the soil has a positive effect in reducing nematode infestation. The aim of this study was to evaluate the effect of the addition of organic residue on the reproduction of Meloidogyne javanica and its role in the physiology of the gilo. One-litre pots, each containing one gilo seedling, were inoculated with 5000 eggs of M. javanica and the following treatments evaluated: 1) no inoculation and no residue (NIR); 2) NIR; 3) 12.5 g L-1 poultry manure; 4) 25 g L-1 cattle manure; 5) 20 g L-1 filter cake; 6) 5 g L-1 of the shoots of Tagetes patula; 7) 6.25 g L-1 of the shoots of Brassica oleracea var. capitata; 8) 20 mL L-1 vinasse and 9) 1 mL Abamectin-based commercial product (18 g L-1 a.i.). A randomised block design was used, with six repetitions. Gas exchange variables were evaluated 15, 30 and 45 days after inoculation with the nematode (DAI) and the vegetative and nematological variables at 60 DAI. The treatments that included cattle manure and filter cake afforded the best physiological rate and development in the gilo. The best results in controlling the nematode were given by the poultry manure, cattle manure and filter cake, reducing the reproduction of M. javanica by 41.76, 51.44 and 52.40%, respectively. Based on the results, poultry manure, cattle manure and filter cake are efficient in controlling M. javanica and show potential to be used in the integrated management of M. javanica in the gilo.